2019
DOI: 10.1093/rpd/ncy288
|View full text |Cite
|
Sign up to set email alerts
|

Patient Dose Survey Based on Size-Specific Dose Estimate and Acceptable Quality Dose in Chest and Abdomen/Pelvis Ct Examinations

Abstract: The practical aspects of two recently developed patient dose optimization methods in computed tomography (CT) examinations, size-specific dose estimate (SSDE) and acceptable quality dose (AQD), were verified for the chest and abdomen/pelvis examinations. A dose survey was performed in a CT institute by considering patients lateral diameter, weight and body mass index (BMI). The AQD tables for weight and BMI groups and SSDE threshold curves were obtained. The mean of volume CT dose index and dose length product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
7
1
Order By: Relevance
“…The correlation for the abdominal and for the chest region they found are also seen in our investigations. However, they did not include gender in their study, where our results show a difference between female and male patients ( 15 ) . Xu et al found that the \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\mathrm{BMI}$\end{document} is better suited than body weight to estimate \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\mathrm{SSDE}$\end{document} .…”
Section: Discussionmentioning
confidence: 68%
“…The correlation for the abdominal and for the chest region they found are also seen in our investigations. However, they did not include gender in their study, where our results show a difference between female and male patients ( 15 ) . Xu et al found that the \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\mathrm{BMI}$\end{document} is better suited than body weight to estimate \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\mathrm{SSDE}$\end{document} .…”
Section: Discussionmentioning
confidence: 68%
“…Because the CT scan has the highest accumulated radiation dose among all medical exposures it seems the SSDE will be placed on the CT console as a tools to establishment of DRLs and optimization of protocols in future; thus upgrading and using of this index is necessary. In this study for the first time the DRLs established for head and abdomen-pelvis CT examinations and compared with national DRL and other same studies in Iran (7,15) . Auto exposure control (AEC) adjusts the tube current according the attenuation data from localizer (16) .…”
Section: Discussionmentioning
confidence: 99%
“…As we mentioned in first paragraph the CT scan is responsible for 49% of all medical exposure; thus, for the first DRLs establishment in Ilam we focused on CT scan as the more important modality in medical radiation exposures. Many studies have established the CT scan DRLs in different countries (9)(10)(11)(12) ; also same studies carried out in Iran (1,7,9,13,14) . Sohrabi et al study is the most greatest study in Iran that was carried out in 157 scanner for assessment the radiation dose of head, sinus, chest, and abdomen-pelvis CT examinations to establishment the national DRLs (15) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since SSDE was announced, several softwares have been developed to measure the effective dose and organ dosage based on SSDE [9,10]. Several studies reported that SSDE was used to represent dose optimization values such as diagnostic reference level (DRL) and acceptable quality dose (AQD) [11][12][13][14]. SSDE is estimated from the output dose or the volume CT dose index (CTDI vol ) and patient characteristics.…”
Section: Introduction mentioning
confidence: 99%